Joint impacts of future climate conditions and invasive species on black ash forested wetlands - Shannon, Joseph; Kolka, Randall; Van Grinsven, Matthew; Liu, Fengjing (Frontiers in Forests and Global Change, 2022)
Wetlands around the globe are being impacted by changing temperature and precipitation patterns. Simultaneously black ash forested wetlands are expected to lose much of their overstory canopy due to the invasive Emerald Ash Borer (EAB). Field experiments and modeling efforts have provided information on species tolerance of post-EAB conditions and future climate adapted species. No studies have yet examined the interaction of the loss of ash and future climate scenarios on wetland hydrologic conditions. We developed daily wetland hydrology models for three vegetation conditions: black ash forest, non-ash future forest, and non-forested. Model simulations were evaluated under current climate conditions and under two future climate scenarios representing warm & dry (T: +1.9 C, P: -2.6 cm) or hot & wet (T: +8.9 C, P: +6.2 cm) scenarios. For each combination of vegetation condition and climate scenario, 10,000 annual synthetic weather sequences were used as inputs to the wetland hydrology models. Simulated wetland hydrology remained highly variable based on seasonal precipitation and evaporative demand. We compared the occurrence probability of stream-network connectivity, surface inundation, and dry conditions. Effects ranged from slightly drier under non-forested and warm & dry conditions to much wetter under future-forested and hot & dry conditions. Non-forested conditions resulted in 15 and 20% more daily observations of connectivity to stream networks and surface water, and 7% fewer daily observations of dry conditions. Future-forested conditions resulted in larger impacts: 40 and 35% more daily observations of connectivity to stream networks and surface water and 10% fewer daily observations of dry conditions. Projected climate change-induced water deficits resulted in 10 –25% fewer days with connectivity and surface water and 5–10% more days with dry conditions (dependent on future scenario). Our results show vegetation change as an equal or greater individual driver of future hydrologic conditions in black ash wetlands relative to climate change. Non-forested conditions and projected climate change-induced impacts each effectively negated the other. Management decisions around vegetation transition and establishment should consider the interaction with future climate scenarios, and the large effect that poorly inundation-adapted plant communities could have on hydrologic conditions.